2013
DOI: 10.3989/gya.072812
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chicken fat as adulterant in butter using fourier transform infrared spectroscopy and chemometrics

Abstract: Butter may be adulterated with cheaper animal fats, such as chicken fat (CF). Thus, the detection and quantification of butter adulteration with CF was monitored using Fourier transform infrared (FTIR) spectroscopy, combined with chemometric of partial least square (PLS) at the frequency regions of 1200-1000cm–1. FTIR measurements were made on pure butter and that adulterated with varying concentrations of CF (0-100% w/w in butter). PLS calibration exhibits a good relationship between actual and FTIR predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…On the FTIR records, seven characteristic peaks were found in all hydrolyzed fats; the model representation is shown in Figure 3. For comparison, five peaks were selected, with reference values and molecular action of individual peaks [42][43][44][45][46][47], which are recorded in Table 4. For these peaks, their absorbance changed the most.…”
Section: Vibrational Characterization Of Functional Groupsmentioning
confidence: 99%
“…On the FTIR records, seven characteristic peaks were found in all hydrolyzed fats; the model representation is shown in Figure 3. For comparison, five peaks were selected, with reference values and molecular action of individual peaks [42][43][44][45][46][47], which are recorded in Table 4. For these peaks, their absorbance changed the most.…”
Section: Vibrational Characterization Of Functional Groupsmentioning
confidence: 99%
“…Analysis of chicken fat adulteration in butter FTIR, GC-FID PLS FTIR spectrum at fingerprint region of (1200-1000 cm −1 ). [118] PLS can be successfully used to quantify the level of chicken fat adulterant with R 2 of 0.981 at the selected fingerprint region of 1200-1000 cm −1 .…”
Section: Purpose Of Analysis Main Instrument Statistical Analysis Markers/differentiation Features References Highlightmentioning
confidence: 99%
“…FTIR, GC-FID PLS FTIR spectrum at fingerprint region of (1200-1000 cm −1 ). [118] PLS can be successfully used to quantify the level of chicken fat adulterant with R 2 of 0.981 at the selected fingerprint region of 1200-1000 cm −1 . Chicken fat may serve as a potential adulterant in canola oil [114], butter [118], and also cod liver oil [116], owing to its highly identical fatty acid profiles and low cost.…”
Section: Analysis Of Chicken Fat Adulteration In Buttermentioning
confidence: 99%
See 1 more Smart Citation
“…According to [1] reported that the optimization of FTIR wave number in the detection beef fat in butter at wave number 1500-1000 cm -1 . Reference [5] also reported that the optimization of FTIR in the chicken detection in butter at wave number 1200-1000 cm -1 . The other research from [6] reported that FTIR wave number region at 4000-650 cm -1 This research was aimed to optimize of wave number of FTIR for detection of lard in CPO.…”
mentioning
confidence: 99%